Laparoscopic urogynecology principles and practice - Deval, Bruno; Jeffery, Stephen; O'Reilly, Barry; Paraiso, Marie Fidela R.; Phillips, Christian Hambro (Cambridge University Press, 2022)
Laparoscopic surgery for the treatment of disorders such as urinary incontinence and pelvic organ prolapse is evolving rapidly with few resources available for clinicians. This text will act as a gold standard reference in the field of laparoscopic urogynaecological surgery. The introductory section covers the basics of laparoscopy, including patient selection, surgical set up and the prevention and management of complications. Further sections focus on different "gold standard" techniques and the procedural steps needed to perform the surgery, including chapters on colposuspension, paravaginal repair, laparoscopic hysterectomy as well as apical suspensory surgery such as sacrocolpopexy and sacrohysteropexy. The final section includes debates and opinion pieces on newer techniques as well as discussion on the use of mesh in treating pelvic organ prolapse. There is also a section addressing the current rise in robotic surgery. The editors and contributors are all experts in the field, providing an authoritative and global view on techniques. Highly illustrated, with videos demonstrating the techniques, this is an eminently practical guide to the use of laparoscopy in urogynaecology.